Study of the Persian Gulf coastal jets under the influence of thermocline using numerical simulation - Hesameddin Mehrfar; Masoud Torabi Azad; Kamran Lari; Abbas-Ali Ali-Akbari Bidokhti (نشریه مهندسی دریا, 2020)
Seasonal circulation of coastal currents of the Persian Gulf with a horizontal resolution of 2-minutes of latitude and longitude was simulated using COHERENS numerical model. The currents of the Iranian coasts flew northwestward from January to April, reaching the highest level from June to August, when surface inflow currents through the Strait of Hormuz gradually became stronger with establishment of the seasonal thermocline. The simulation results indicated thermocline expansion with the onset of the heating season. Under the mentioned conditions, stronger coastal currents were generated in summer. The simulation results showed the presence of coastal jet with a speed of approximately 30 cm/s from May to October. The coastal jet near the Iranian coasts is only confined to the surface, moves toward southeast; however, the coastal jet in the vicinity of Saudi Arabia is entirely present at all columns of water from surface to the seabed and moves toward southeast.